1980
DOI: 10.1029/ja085ia02p00613
|View full text |Cite
|
Sign up to set email alerts
|

The formation of ducts and spread F and the initiation of bubbles by field‐aligned currents

Abstract: Magnetospheric ducts for medium frequency (MF) radio waves are formed, for L •> 1.2, between about 20 and 22 hours local time. Their occurrence frequency remains constant for the remainder of the night and begins to decrease after sunrise. This decrease continues until near sunset. The seasonal and longitudinal variation of the ducts and of low-latitude spread F implies that both are related to hemispheric asymmetry of the winds in the dynamo region and hence are probably generated by field-aligned currents as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…However, the ROCSAT spacecraft at ∼600 km can see density enhancements associated with the depletion structures that rise to ∼1000 km. Previous observations showed that most depletion structures rise to maximum height up to ∼1000 km, although they have been observed up to 3000 km [ Burke et al , 1979; Muldrew , 1980a]. Thus the lower orbit ROCSAT spacecraft would observe the density enhancements more frequently than the DMSP spacecraft.…”
Section: Discussion and Summarymentioning
confidence: 91%
“…However, the ROCSAT spacecraft at ∼600 km can see density enhancements associated with the depletion structures that rise to ∼1000 km. Previous observations showed that most depletion structures rise to maximum height up to ∼1000 km, although they have been observed up to 3000 km [ Burke et al , 1979; Muldrew , 1980a]. Thus the lower orbit ROCSAT spacecraft would observe the density enhancements more frequently than the DMSP spacecraft.…”
Section: Discussion and Summarymentioning
confidence: 91%
“…The characteristics and morphology of these depletions, that has been obtained mainly with the Jicamarca radar (e.g. Woodman and La Hoz, 1976), and substantiated by the satellite-based instruments and Altair radar observations (McClure et al, 1977;Dyson and Benson, 1978;Muldrew, 1980;Tsunoda, 1980;Tsunoda et al, 1982;Kil and Heelis, 1998;Yeh et al, 2001), are very well documented. Theoretical and observational investigations indiCorrespondence to: R. Pandey (pandey r@yahoo.com) cate that these depletions are generated on the bottomside of the nighttime equatorial F region and rise to higher altitudes due to the non-linear evolution of the generalized RayleighTaylor and E×B plasma instabilities (Kelley, 1989;Fejer et al, 1999).…”
Section: Introductionmentioning
confidence: 92%
“… Calvert [1981] suggested that R ‐ X waves ducted in FAI would be readily detectable. Evidence of ducting has been observed in the ionosphere for L ‐ O and R ‐ X modes [see, e.g., Muldrew , 1963, 1967, 1980] and in the magnetosphere for whistlers [e.g., Angerami , 1970; Carpenter , 1981; Carpenter and Sulic , 1988]. Only a few percent N e enhancement is required for effective whistler ducting [e.g., Smith , 1961; Helliwell , 1965], and a similar N e depletion for L ‐ O and R ‐ X mode ducting [see, e.g., Muldrew , 1963, 1967; Platt and Dyson , 1989; Calvert , 1995].…”
Section: Introductionmentioning
confidence: 99%